Evaluation of Construction Provisions to Avoid Cracking in Masonry Partitions Affected by Structural Deformations of Concrete Slabs - Rui Sousa (2019)
Partitions walls can be damaged and crack when affected by the deformation of structural elements during their use in buildings. Masonry is the most common solution used for partitions. However, giving their brittle behavior, construction provisions to avoid cracking may have to be evaluated and implemented in these walls. In this paper, a numerical study was conducted to evaluate the susceptibility of cracking of traditional Portuguese masonry partitions affected by vertical deformations of concrete slabs during serviceability conditions (with and without creep effects). Two different modeling approaches were used: simulation of a concrete structure interacting with the unreinforced masonry partitions constructed with lateral or top movement joints, and another simulation of isolated masonry deep beams constructed with and without reinforcements. The most common construction solutions used in Portuguese buildings for structural systems, partition walls and reinforcement techniques (reinforcement of mortar bed joints and mortar coatings) were used in these simulations. To simulate the behavior of masonry panels, a non-linear model calibrated with experimental results was used, a linear elastic model was assumed for the concrete structure and an elastic-plastic model was used for the steel reinforcements. The effect of creep in the masonry and concrete was calculated according to European standard calculation methodologies. The results obtained demonstrated that the use of reinforcement techniques can be a solution to increase the strength and deformation of these walls in order to avoid cracking, as well as the use of movement joints and a proper control of structural deformations. Some recommendations are suggested.